Performance Improvement of DC Motor by using ANFIS Controller - Basha, Mulla Gouse; Chenchireddy, Kalagotla; Ahmed Sydu, Shabbier; sultana, waseem; Kumar, V; Ganesh, Lukka Bhanu (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
This research paper is to improve a DC motor's performance by using two different control strategies: Sliding Mode Control (SMC) and ANFIS. Fuzzy Logic (FL) and Neural Networks (NN) are used by the ANFIS controller to show flexibility in the face of nonlinearities, and SMC shows resilience in the face of uncertainty. The dynamic response of the armature current and DC motor speed under each control technique is shown by the simulation results. By highlighting the benefits and drawbacks, comparative analysis helps to choose the best control strategy for a given set of application needs.